Pengembangan Buku Ajar Strategi Pembelajaran Ekonomi Berbasis Project - Nurlaili, Eka Indah; Dewi, Retno Mustika; Ghofur, Muhammad Abdul (Fakultas Ekonomi Universitas Pendidikan Ganesha, 2024)
The Economics Learning Strategy course is an elective course taken by students of the S1 Economics Education Study Program FEB UNESA. The characteristics of this course are not only planning activities to economic learning, but also provide instructions for designing learning activities and practicing how to carry out good economic learning to support effectiveness and efficiency to achieve lecture goals. Learning is arranged in a project-based RPS. A practical means of learning interaction is needed, namely relevant teaching materials in the form of textbooks. The method used in the development of this textbook is the ADDIE Model with the formulation of analysis, design, development, implementation, evaluation. From the results of expert validation, the feasibility level of the textbook is 79% for the material component, 77% for the presentation component, 72% for the language component, and 80% for the graphic component. Thus, it can be concluded that the textbooks developed are feasible Most of the students in the limited trial gave positive responses to all aspects of assessment. Textbook development is beneficial for students to learn independently.